Management of non-metastatic castrate-resistant prostate cancer: A systematic review. (November 2018) - Loriot, Yohann; Supiot, Stéphane; Beauval, Jean-Baptiste; Schlürmann, Friederike; Pasticier, Gilles; Sargos, Paul; Barthélémy, Philippe; Pignot, Géraldine; Maillet, Denis; Vincendeau, Sébastien; Gross, Emmanuel; Ploussard, Guillaume; et al.
Highlights: nmCRPC is a heterogeneous stage of prostate cancer for which the challenge is to delay the onset of metastasis. Until recently, few evidences were available to orient clinicians in the choice of treatment modalities. Recent results obtained with next generation antiandrogen therapy demonstrate for the first time a survival benefit in this setting and will modify the management of nmCRPC. New imaging technics will help improving diagnosis of prostate cancer and thus aid in determining the best treatment option. Abstract: Management of non metastatic castrate resistant prostate cancer is challenging for clinicians due to the heterogeneity of the disease and to the scarce clinical data available in this setting. Recent results obtained with the new generation hormone therapies (NGHT) apalutamide and enzalutamide bring a new perspective for the treatment strategy. The authors present here a systematic review of the treatment options.